Drug Supply System in the Pharmacy â€œThe Medicine Shoppeâ€ with Visual Basic 6.0 Applications - Yuli Daniati Riska, 30403145 (Jurnal Sistem Informasi, 2007)
Shoppe pharmacy the medicine which is developing its business in the field of drug supply,Â which at this pharmacy data processing information on the drug supply is still processedÂ records recorded in penginputan, editing, to produce the report. By using the applicationÂ programming Â Microsoft Â Visual Â Basic Â 6.0. Â Will Â facilitate Â the Â administration Â to Â doÂ penginputan, editing, from a good data and the data supplier of medical supplies.Â